The Impact of Occupational Characteristics and Victimization on Job Burnout Among South Korean Correctional Officers - Choi, Jaeyong (Criminal justice and behavior, 2020)
Prior research on correctional officer burnout has focused almost exclusively on the effects of job characteristics. To date, this line of inquiry has largely failed to consider one important factor associated with the unique nature of prison work—direct exposure to interpersonal victimization (e.g., individuals in custody-on-officers). This article uses data from 269 correctional officers working in four South Korean facilities to examine the differential impact of experienced individuals in custody-on-officers aggression (i.e., verbal violence, minor and serious physical violence) and job characteristics (e.g., role clarity) on three dimensions of job burnout (i.e., emotional exhaustion, depersonalization, and a sense of a lack of personal accomplishment). Results show that verbal victimization is more impactful on correctional officer burnout than physical victimization. However, the results also suggest that job characteristics may be more impactful on predicting certain dimensions of correctional officer burnout than experienced victimization. Potential policy implications are discussed.